ANALISIS POLA PENEMPATAN DAN JUMLAH STASIUN HUJAN BERDASARKAN PERSAMAAN KAGAN PADA DAS KEDUANG WADUK WONOGIRI - Pariarta, Putu Gustave Suriantara (Jurnal Ilmiah Teknik Sipil, 2012)
Abstract : Precipitation measurement accuration is affected by the amount of rainfall stations and the network pattern within basin area. The precise placement of rainfall stations considering location, amount of rainfall stations, network pattern will contribute to the data accuration of rainfall depth, spreads and rainfall intensity. There is no standard yet for the number of rainfall stations that can represent rainfall variability in watershed, so to obtain the optimal number and network pattern of rainfall stations must based on calculation. The measurement for network density of rainfall stations is calculated using Kagan method because using this method the optimal number and network pattern can be obtained. The calculation begins with determining the correlation coeffitient between rainfall stations as an input to monthly rainfall. In this stage, the complete dry days were not counted, but only wet days or months with high rainfall intensity. The evaluation of Kagan method produced first output which is the correlation between number of the required rainfall station with certain level of error (average error and interpolation error) and the second which is the location of rainfall station refers to a certain pattern. The output from Kagan method is the optimal number and network pattern of rainfall station. The analysis shows that there is lacks of rainfall station both by adjustment error of 5 % using 68 rainfall stations with 2,591 km bond length and adjustment error of 10 % using 17 rainfall stations 17 with 5,319 km bond length.
Keywords: stasiun hujan, metode kagan, kesalahan perataan